Hubungan Lama Penggunaan Smartphone dan Stres dengan Kejadian Insomnia pada Mahasiswa Kebidanan di Sekolah Tinggi Ilmu Kesehatan Mitra Sejati - Suryani; Adelina Fitri Tanjung; Eka Ristin Tarigan (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Insomnia is a sleep disorder experienced by a person that causes sleep needs to not be met in quantity or quality. The aim of the research was to analyze the relationship between duration of smartphone use and stress with the incidence of insomnia in midwifery students at the Mitra Sejati College of Health Sciences. This study used a quantitative research design with a cross sectional study design. The population in this study were all 74 midwifery students at Mitra Sejati College of Health Sciences. The sampling technique in this research was total sampling. The results of the bivariate analysis based on the results of chi square test showed that there was a significant relationship between duration of smarthphone use and the incidence of insomnia (p=0.023<0.05) and there was a relationship between stress and the incidence of insomnia (p=0.004<0.05). It is recommended for students to reduce excessive use of smartphones, especially at night so as not to interfere with lecture activities, and to keep themselves busy with other activities such as sports, reading books, and othe active campus activities.